Default risk sharing between banks and markets: The contribution of collateralized debt obligations - Günter Franke; Jan Pieter Krahnen (University of Konstanz, Center of Finance and Econometrics (CoFE), 2005)
This paper contributes to the economics of financial institutions risk management by exploring how loan securitization affects their default risk, their systematic risk, and their stock prices. In a typical CDO transaction a bank retains through a first loss piece a very high proportion of the default losses, and transfers only the extreme losses to other market participants. The size of the first loss piece is largely driven by the average default probability of the securitized assets. If the bank sells loans in a true sale transaction, it may use the proceeds to expand its loan business, thereby affecting systematic risk. For a sample of European CDO issues, we find an increase of the banks' betas, but no significant stock price effect around the announcement of a CDO issue.
urn:nbn:de:bsz:352-opus-17796
Keywords: D82; G21; D74; 330; Kreditrisiko; Kreditgeschäft; Risikomanagement